Cultivating insight and engagement: exploring the role of Trait Emotional Intelligence in Chinese art education - Wang, Cong (Frontiers in Psychology, 2024)
Background The present study focuses on the unique role of insight and Trait Emotional Intelligence in the realm of art education in China. Insight, traditionally associated with clinical outcomes such as mastering symptoms, developing adaptive behaviors, and enhancing quality of life, is newly contextualized in this study within the framework of art education. The expansion of insight research into areas like Social Psychology reflects its relevance beyond clinical settings, particularly in educational environments where creativity and emotional intelligence are pivotal. Aim In Chinese art education, insight is crucial not just for personal growth but also for professional development, integrating the understanding of emotions, culture, and artistic expression. This study explores how Trait Emotional Intelligence fosters insight and engagement in art students, underscoring its transformative impact on their educational and professional journey in the art world. Methods Using a sample of Chinese art education students at University level (N = 881), that answered a quantitative self-report questionnaire, statistical procedures are applied to test the relationships between Trait Emotional Intelligence, Insight orientation, and students’ academic engagement. Results In the structural model, the path from Trait Emotional Intelligence to Insight Orientation was significant, indicating a positive relationship. Students’ Engagement was significantly predicted by Insight Orientation and Trait Emotional Intelligence. Implications This finding corroborates theoretical assertions that individuals with higher emotional intelligence are more inclined to have enhanced insight. The findings of the present study extend beyond the field of Art education, allowing us to provide a broad spectrum of social implications for Higher Education institutions.